Comparison of Lumbar Total Disc Replacement With Surgical Spinal Fusion for the Treatment of Single-Level Degenerative Disc Disease: A Meta-Analysis of 5-Year Outcomes From Randomized Controlled Trials. Issue 4 (June 2018) - Zigler, Jack; Gornet, Matthew F.; Ferko, Nicole; Cameron, Chris; Schranck, Francine W.; Patel, Leena
Study Design: Meta-analysis. Objectives: To evaluate the long-term efficacy and safety of total disc replacement (TDR) compared with fusion in patients with functionally disabling chronic low back pain due to single-level lumbar degenerative disc disease (DDD) at 5 years. Methods: PubMed and Cochrane Central Register of Controlled Trials databases were searched for randomized controlled trials reporting outcomes at 5 years for TDR compared with fusion in patients with single-level lumbar DDD. Outcomes included Oswestry Disability Index (ODI) success, back pain scores, reoperations, and patient satisfaction. All analyses were conducted using a random-effects model; analyses were reported as relative risk (RR) ratios and mean differences (MDs). Sensitivity analyses were conducted for different outcome definitions, high loss to follow-up, and high heterogeneity. Results: The meta-analysis included 4 studies. TDR patients had a significantly greater likelihood of ODI success (RR 1.0912; 95% CI 1.0004, 1.1903) and patient satisfaction (RR 1.13; 95% CI 1.03, 1.24) and a significantly lower risk of reoperation (RR 0.52; 95% CI 0.35, 0.77) than fusion patients. There was no association with improvement in back pain scores whether patients received TDR or fusion (MD −2.79; 95% CI −8.09, 2.51). Most results were robust to sensitivity analyses. Results for ODI success and patient satisfaction were sensitive to different outcome definitions but remained in favor of TDR. Conclusions: TDR is an effective alternative to fusion for lumbar DDD. It offers several clinical advantages over the longer term that can benefit the patient and reduce health care burden, without additional safety consequences.